(untitled) (Bangladesh Veterinarian, 2016)
To determine the microbial load of hog plum (Spondias mombin) (Local name Amra) sold by street vendors at Bangladesh Agricultural University (BAU) campus and Mymensingh city, samples of raw hog plum wash (n = 5), hand wash of vendors (n = 5), knife wash (n = 5) and stick wash (n = 5) were collected from five different hog plum vendors. Microbial quality of hog plums was assessed by total viable count (TVC), total coliform count (TCC) and total staphylococcal count (TSC). Samples were inoculated into Eosin Methylene Blue (EMB) agar, MacConkey agar and Mannitol Salt (MS) agar. Identification of Staphylococcus aureus and Escherichia coli (E. coli) were confirmed by sugar fermentation and biochemical tests. TVC ranged from log 6.9 to 6.8 cfu/mL in raw hog plum wash, log 6.9 to 5.8 cfu/mL in vendors’ hand wash, log 5.9 to 4.9 cfu/mL in stick wash and log 5.3 to 5.2 cfu/mL in knife wash samples. TCC of raw hog plum wash sample was log 3.4 to 2.3 cfu/mL and in vendors hand wash samples log 3.4 to 1.3 cfu/mL. TCC were not detected in stick and knife wash samples. TSC ranged from log 4.6 to 4.6 cfu/mL in raw hog plum wash, log 5.7 to 4.6 cfu/mL in vendors’ hand wash, log 4.6 to 3.6 cfu/mL in stick wash and log 4.5 to 4.5 cfu/mL in knife wash samples. Staphylococcus aureus were sensitive to ciprofloxacin, gentamicin and vancomycin and resistant to ampicillin and cephalexin. E. coli were sensitive to ciprofloxacin and gentamicin and resistant to ampicillin, penicillin G and cephalexin. It is indicated that hog plum sold at BAU campus and Mymensingh city street harbour multidrug-resistant food-borne bacteria causing possible public health hazards. Bangl. vet. 2015. Vol. 32, No. 1, 19-26